2019
DOI: 10.1371/journal.pone.0210655
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section on a rise—Does advanced maternal age explain the increase? A population register-based study

Abstract: BackgroundIn Denmark, the cesarean section rate has increased by 49% between 1998 and 2015 and accounts for 21% of all births. Cesarean sections may cause short- as well as long-term consequences for both the mother and the child and impose further risks in future pregnancies. Delaying pregnancy until advanced maternal age at childbirth has been suggested as contributing to the increase. The proportion of women giving birth at 35 years or above increased from 15% (1998) to 21% (2015). Advanced maternal age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
103
5
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 44 publications
13
103
5
6
Order By: Relevance
“…Several previous studies document a significant association between advanced maternal age (>35 years) and an increased likelihood of CS birth [19,20]. This association may be interpreted as a result of a changing social environment, but a common explanation is the pre-pregnancy morbidities associated in these cases [21]. However, as noted in Table 4, only a few women that constitute our study presented comorbidity and, none of them had the age reported, as was not required for the RTGCS.…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies document a significant association between advanced maternal age (>35 years) and an increased likelihood of CS birth [19,20]. This association may be interpreted as a result of a changing social environment, but a common explanation is the pre-pregnancy morbidities associated in these cases [21]. However, as noted in Table 4, only a few women that constitute our study presented comorbidity and, none of them had the age reported, as was not required for the RTGCS.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, our results suggest a multifaceted approach to define AMA in today’s society. Ideally, this should help spare both physicians and patients from ungrounded fears related to ENM, which has been shown to lead to unreasonably low thresholds for obstetric intervention and primary cesarean section 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The finding of higher cesarean rates for Black mothers is consistent with prior research [ 37 39 ], though the differences identified here (aOR 2.40) after adjustment are greater than in those studies. Likewise, the finding of higher cesarean rates for older [ 40 ] and less educated mothers has been regularly confirmed [ 41 ]. The positive relationship between age and cesarean birth appears to be well-established [ 18 ].…”
Section: Discussionmentioning
confidence: 94%